D-Serine metabolism in C6 glioma cells: Involvement of alanine-serine-cysteine transporter (ASCT2) and serine racemase (SRR) but not D-amino acid oxidase (DAO) - Sikka, Pilleriin (Wiley Subscription Services, Inc., A Wiley Company, 2010)
D-serine is an endogenous N-methyl-D-aspartate (NMDA) receptor coagonist. It is synthesized from L-serine by serine racemase (SRR), but many aspects of its metabolism remain unclear, especially in the forebrain, which lacks active D-amino acid oxidase (DAO), the major D-serine degradative enzyme. Candidate mechanisms include SRR operating in α,β-eliminase mode (converting D-serine to pyruvate) and regulation by serine transport, in which the alanine-serine-cysteine transporter ASCT2 is implicated. Here we report studies in C6 glioma cells, which “simulate” the forebrain, in that the cells express SRR and ASCT2 but lack DAO activity. We measured D-serine, ASCT2, SRR, and DAO expression and DAO activity in two situations: after incubation of cells for 48 hr with serine isomers and after increased or decreased SRR expression by transfection and RNA interference, respectively. Incubation with serine enantiomers decreased [(3)H]D-serine uptake and ASCT2 mRNA and increased SRR immunoreactivity but did not alter DAO immunoreactivity, and DAO activity remained undetectable. SRR overexpression increased D-serine and pyruvate and decreased [(3)H]D-serine uptake and ASCT2 mRNA but did not affect DAO. SRR knockdown did not alter any of the parameters. Our data suggest that D-serine transport mediated by ASCT2 contributes prominently to D-serine homeostasis when DAO activity is absent. The factors regulating D-serine are important for understanding normal NMDA receptor function and because D-serine, along with DAO and SRR, is implicated in the pathogenesis and treatment of schizophrenia. © 2010 Wiley-Liss, Inc.